KEGIATAN FISIOTERAPI GERIATRI PADA LANSIA DENGAN GANGGUAN KUALITAS TIDUR DI PUSKESMAS KENDALSARI KOTA MALANG - Tri Wahyuni, Andriani; Rosidah, Nikmatur; Suharto, Bonita (Medic Nutricia : Jurnal Ilmu Kesehatan, 2025)
Counseling and counseling are carried out with the aim of providing education on the puzzle of sleep quality disorders in the elderly regarding the causes of sleep disorders to how to overcome sleep disorders themselves, provision is also carried out for the elderly so that they can do independent exercises at home to alleviate the effects of sleep disorders experienced. Relieve complaints of sleep disorders in the elderly and education about exercises that can be applied independently at home. Provide counseling and counseling related to sleep disorders in the elderly using leaflets and questions and answers to the elderly and families about things that are known about sleep quality. The Pittsburgh Sleep Quality Index (PSQI) questionnaire was also filled out to determine the condition of the elderly's sleep quality. Counseling and counseling activities can increase the knowledge of both the elderly and their families about the importance of maintaining sleep quality and how to prevent sleep quality, there is a significant change where there is an increase in sleep hours in the elderly who experience sleep disorders and no longer wake up often at night.